2008
DOI: 10.1063/1.3029745
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a bimodal eutectic structure on the plasticity of a (Ti70.5Fe29.5)91Sn9 ultrafine composite

Abstract: Systematic investigations on the microstructural evolution of a bimodal eutectic (Ti70.5Fe29.5)91Sn9 ultrafine composite containing Ti3Sn dendrites upon compression reveal that local deformation of the dendrites dominates the early stage of deformation with a plastic strain of εp=5.8%. After further deformation (εp=10.2%), a wavy propagation of shear bands indicative of dissipation of the shear stress is caused by a rotation of the coarse eutectic structure along the interfaces of the bimodal eutectic structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…Whereas, the improvement of compressive plasticity of UECs have been interlinked with the formation of large number of shear bands [28,29], and localized rotation of the colony boundaries to effectively dissipate the shear stress [10,11,[20][21][22]25], which have been further assisted due to the change in the lamellar morphology upon alloy additions [21]. Hence, the ternary alloy addition must tuned the lamellar microstructure in UECs, and has tailored their mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas, the improvement of compressive plasticity of UECs have been interlinked with the formation of large number of shear bands [28,29], and localized rotation of the colony boundaries to effectively dissipate the shear stress [10,11,[20][21][22]25], which have been further assisted due to the change in the lamellar morphology upon alloy additions [21]. Hence, the ternary alloy addition must tuned the lamellar microstructure in UECs, and has tailored their mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Along this line, Ti-Fe-based UEC with FeTi and metastable b-Ti lamellae in their microstructure, has been reported to show high compressive strength $1800 MPa and large plasticity ($15%) [13][14][15][16][17]. The effects of various alloy additions, such as, Co, Cu, V, Sn, Ni, and B on the mechanical properties and microstructure of Ti 70.5 Fe 29.5 UEC without presence of any micrometer-size toughening phase, have been studied [10,[18][19][20][21]. It has been revealed that Sn refines the eutectic lamellar spacing and improves the plasticity [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these results, it is noted that addition of Si in Fe 70 Ni 15 B 15 alloy changes nanostructure-dendrite structure to bimodal eutectic structure with spherical eutectic colony. It has been reported that the plasticity of the ultrafine eutectic composite can be enhanced by rotation of spherical eutectic colony resulting in effective dissipation of the shear localization [17,18,25]. Therefore, it is believed that the dimple-like morphology on the fracture surface results from the rotation of the eutectic colonies.…”
Section: Methodsmentioning
confidence: 97%
“…Alternatively, a series of Ti-based nanostructuredendrite composites consisting of micron-scale dendrites in the nanostructured matrix has been developed through a solidification method based on the systematic alloy design [12][13][14]. Also, Tibased eutectic alloys having ultrafine lamellar structure have been developed to effectively enhance both strength and plasticity of materials [15][16][17][18][19][20]. More recently, the microstructural investigation of a Ti 93 Co 7 alloy reveals that the widmanstä tten-type u phase forms heterogeneously along the boundaries of large b-Ti grains upon solidification and, the (u þ b-Ti) microstructure dynamically transforms into a bimodal grain structure during deformation resulting in the enhancement of the plasticity as well as the strength of the alloy [21].…”
mentioning
confidence: 99%